FRET enhancement close to gold nanoparticles positioned in DNA origami constructs. Issue 2 (12th December 2016) - Aissaoui, Nesrine; Moth-Poulsen, Kasper; Käll, Mikael; Johansson, Peter; Wilhelmsson, L. Marcus; Albinsson, Bo
Abstract : The energy transfer rate of a FRET pair is enhanced when positioned in close proximity to 5 nm gold nanoparticle on a DNA origami. Abstract : Here we investigate the energy transfer rates of a Förster resonance energy transfer (FRET) pair positioned in close proximity to a 5 nm gold nanoparticle (AuNP) on a DNA origami construct. We study the distance dependence of the FRET rate by varying the location of the donor molecule, D, relative to the AuNP while maintaining a fixed location of the acceptor molecule, A. The presence of the AuNP induces an alteration in the spontaneous emission of the donor (including radiative and non-radiative rates) which is strongly dependent on the distance between the donor and AuNP surface. Simultaneously, the energy transfer rates are enhanced at shorter D–A (and D–AuNP) distances. Overall, in addition to the direct influence of the acceptor and AuNP on the donor decay there is also a significant increase in decay rate not explained by the sum of the two interactions. This leads to enhanced energy transfer between donor and acceptor in the presence of a 5 nm AuNP. We also demonstrate that the transfer rate in the three "particle" geometry (D + A + AuNP) depends approximately linearly on the transfer rate in the donor–AuNP system, suggesting the possibility to control FRET process with electric field induced by 5 nm AuNPs close to the donor fluorophore. It is concluded that DNA origami is a very versatile platform for studying interactions between molecules and plasmonic nanoparticles in general and FRET enhancement in particular.